Side effects of chronic systemic glucocorticoid therapy: what dermatologists should know - Lucas Campos Prudente Tavares; Lívia de Vasconcelos Nasser Caetano; Mayra Ianhez (Anais Brasileiros de Dermatologia, 2024)
Abstract In dermatologists' clinical practice, the use of systemic glucocorticoids is recurrent for the management of different comorbidities that require chronic immunosuppression. The prescription of this medication requires caution and basic clinical knowledge due to the several adverse effects inherent to the treatment. However, different doubts may arise or inappropriate conduct may be adopted due to the lack of objective and specific guidelines for the screening, prophylaxis and management of complications from chronic corticosteroid therapy. Considering this problem, the authors carried out a narrative review of the literature to gather up-to-date data on adverse effects secondary to the chronic use of systemic glucocorticoids. The broad approach to this topic made it possible to review the pathophysiology and risk factors for these complications, as well as to develop updated orientation that can be used as a learning tool and quick reference for dermatologists during their clinical practice with glucocorticoids.